Opportunities to support beginning farmers and ranchers in the 2023 Farm Bill. Issue 3 (29th March 2022) - Jablonski, Becca B. R.; Key, Nigel; Hadrich, Joleen; Bauman, Allie; Campbell, Sarah; Thilmany, Dawn; Sullins, Martha
Abstract: Beginning farmers and ranchers represent an important segment of U.S. agriculture, yet they face financial challenges relative to more established operations. This article provides an overview of emerging research on the financial performance of beginning farm and ranch operations, with a lens toward implications for the 2023 Farm Bill. First, we use U.S. Department of Agriculture (USDA) Agricultural Resource Management Survey data to explore descriptive statistics relative to beginning farm and ranch usage of: local food markets, Federal crop insurance, and financing mechanisms. Subsequently, we leverage a farm‐level panel dataset from the USDA Census of Agriculture and regression analysis to examine the relationship between key financial metrics and beginning farmer success. Results show: (a) beginning farm performance over time is associated with both increases in scale and productivity, as well as participation in agricultural programs, (b) access to credit is important, and that being credit constrained lowers the probability of survival, growth, and success for beginning operations, and (c) beginning operations are significantly less likely to use Federal crop insurance compared to established operations across all scales.